Analysis of QoS parameter in AODV a DSR in mobile Ad Hoc networks - Enciso Quispe, L. (2012)
Providing QoS in the context of Ad Hoc networks includes a very wide field of application from the perspective of every level of the architecture in the network. Saying It in another way, It is possible to speak about QoS when a network is capable of guaranteeing a trustworthy communication in both extremes, between any couple of the network nodes by means of an efficient Management and administration of the resources that allows a suitable differentiation of services in agreement with the characteristics and demands of every single application. The principal objective of this article is the analysis of the quality parameters of service that protocols of routering reagents such as AODV and DSR give in the Ad Hoc mobile Networks; all of this is supported by the simulator ns-2. Here were going to analyze the behavior of some other parameters like effective channel, loss of packages and latency in the protocols of routering. Were going to show you which protocol presents better characteristics of Quality of Service (QoS) in the MANET networks.